2016
DOI: 10.5664/jcsm.5402
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Gastroesophageal Reflux in Obstructive Sleep Apnea: Airway Obstruction or Obesity?

Abstract: Study Objectives: This is the first study to compare reflux events during wake and sleep in obese and non-obese individuals with obstructive sleep apnea (OSA) and obese individuals without OSA. The primary aim of the study was to investigate any additive effect of OSA on gastroesophageal reflux (GER) above that of obesity. Methods: Twenty obese individuals (body mass index, BMI > 30 kg/m 2 ), 9 non-obese individuals (BMI < 30 kg/m 2 ) with moderate-to-severe OSA, and 17 obese control subjects (BMI > 30 kg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…[16][17][18] The most recent study by Shepherd and Orr reported such fi nding by documenting the nGER by esophageal pH monitoring during polysomnography and suggested that obesity rather than AHI may have a greater role in the relationship between OSA and nGER. 17 This prompted us to perform further subgroup analyses, which revealed that the BMI of our patients with moderate-severe OSA (mean = 34.17 kg/m 2 ) was much higher than those with mild OSA (mean = 28.98 kg/m 2 ). The total AHI revealed a linear positive association with nGER score among patients with moderate to severe OSA (AHI ≥ 15), but not among those with mild OSA (AHI < 15).…”
Section: Discussionmentioning
confidence: 98%
“…[16][17][18] The most recent study by Shepherd and Orr reported such fi nding by documenting the nGER by esophageal pH monitoring during polysomnography and suggested that obesity rather than AHI may have a greater role in the relationship between OSA and nGER. 17 This prompted us to perform further subgroup analyses, which revealed that the BMI of our patients with moderate-severe OSA (mean = 34.17 kg/m 2 ) was much higher than those with mild OSA (mean = 28.98 kg/m 2 ). The total AHI revealed a linear positive association with nGER score among patients with moderate to severe OSA (AHI ≥ 15), but not among those with mild OSA (AHI < 15).…”
Section: Discussionmentioning
confidence: 98%
“…Obesity has an important role in the relationship between OSA and GER. 33 There was no relationship between the presence of GERD, OSArelated variables, and BMI in a study in Korea that used PSG and a questionnaire. 14 Ethnic differences between Eastern and Western populations should be considered.…”
Section: Similar Risk Factors Between Gerd and Osamentioning
confidence: 94%
“…A study using high‐resolution esophageal manometry, 24‐h esophageal pH–impedance monitoring, and PSG showed that BMI significantly predicted the number of acidic reflux events; however, the apnea–hypopnea index (AHI) did not exhibit any significant association with any measure of GER severity. Obesity has an important role in the relationship between OSA and GER . There was no relationship between the presence of GERD, OSA‐related variables, and BMI in a study in Korea that used PSG and a questionnaire .…”
Section: Is There Any Causal Relationship Between Gerd and Osa?mentioning
confidence: 97%
“…The frequent co-occurrence of OSA and GERD may be explained by the following mechanisms. Firstly, GERD and OSA patients had similar risk factors: age, obesity, smoking, and alcohol consumption [8,9]. In addition, strong protective mechanisms for swallowing and esophageal peristalsis decline during sleep, which may delay esophageal acid clearance, thereby increasing acidmucosal contact time [10].…”
Section: Supplementary Informationmentioning
confidence: 99%